Análisis jurídico y doctrinario sobre la violencia filio-parental ejercido por adolescentes en el Ecuador; estrategias de intervención para prevenir este fenómeno social - Aguirre Jiménez, Evelyn Karina (2024)
This legal study is based on the need to evaluate the effectiveness of the Ecuadorian legal framework in the prevention and management of child to parent violence. The awareness and active participation of public administrations, the community and social organizations are essential to develop prevention and intervention strategies that comprehensively address this phenomenon, protecting the rights and well-being of all parties involved. The emergence of this problem dates back to the fact that in recent years there has been a considerable increase in child and parent violence in Ecuador, and its impact significantly dominates the social fabric and family dynamics, not only affecting the health and well-being of the children and parents involved, but also having repercussions within society, Addressing VFP involves considering the legal recognition of this phenomenon, the legal responsibility of child perpetrators, the protection measures available to victims, the intervention of the juvenile justice system, psychological and expert aspects, prevention and education strategies, international comparisons and ethical evaluations and their rights. It is evident that child to parent violence is increasing and has negative repercussions on society, becoming a growing area of concern, therefore, the interest that leads us to develop this research is based on a doctrinal analysis for a better understanding of the causes that generate child to parent violence, This background has allowed me to make proposals of a social order that will allow me to structure public policies to prevent and control the increase of this social phenomenon, as well as to strengthen mechanisms to amend certain violent behaviours of adolescents. The achievement of the proposed objectives was possible thanks to the application of research methods, as well as the use of surveys and interviews as fieldwork with legal and criminology professionals and citizens in general, the results of which served to propose and develop good practices and possible solutions to our aim. In addition, the data obtained highlight the importance of developing a proposal for guidelines aimed at incorporating actions that strengthen the effective utility of efficient policies that are related to tackling the criminal phenomenon.